Prescriber and pharmacy variation in patient adherence to five medication classes measured using implementation during persistent episodes. Issue 7 (13th May 2016) - Genberg, Becky L.; Rogers, William H.; Lee, Yoojin; Qato, Danya M.; Dore, David D.; Hutchins, David S.; Brennan, Troyen; Matlin, Olga S.; Wilson, Ira B.
Abstract: Purpose: The objective of this study was to determine the fraction of variance in patient‐level medication adherence accounted for by prescribers and pharmacies. Methods: We used prescription drug claims paid between January 2010 and July 2011 to a national pharmacy benefits manager to define implementation during persistent episodes. Patients in Massachusetts or Rhode Island covered by Blue Cross Blue Shield of Rhode Island and their prescribers were included. Five drug classes were analyzed: angiotensin converting enzyme (ACE) inhibitors, antihyperglycemics (ANHGs), drugs for prostatic hyperplasia (PH), statins, and levothyroxine (THYR). We performed mixed models with random intercepts (drug, patient, prescriber, and pharmacy) and examined the fraction of variance explained at each level using intraclass correlations. Results: Overall implementation ranged from 87 to 91%. The fraction of the explained variance in implementation to ACEs, ANHG, PH, statins, and THYR accounted for by prescribers was 16.4%, 12.6%, 14.6%, 15.6%, and 15% respectively; and for pharmacies 20.4%, 20%, 15.2%, 10.6%, and 9.4%, respectively. Conclusions: Prescriber and pharmacy effects accounted for a substantial amount of the explained variance in implementation across all five drug classes. Adherence interventions for chronic conditions that target prescribers and pharmacies, in addition to patients, could be effective and efficient. Copyright © 2016 John Wiley & Sons, Ltd.